Case report: Fever- pneumonia- lymphadenectasis- osteolytic- subcutaneous nodule: Disseminated chromoblastomycosis caused by phialophora. Issue 12 (December 2019) - Qiu, Ye; Zhang, Jianquan; Tang, Yanping; Zhong, Xiaoning; Deng, Jingmin
Abstract: Chromoblastomycosis (CBM) is a chronic cutaneous and subcutaneous fungal infection caused by certain dematiaceous fungi (usually Fonsecaea, Phialophora, or Cladophialophora) . Histologically, CBM is characterized by the presence of medlar bodies. However, the diagnosis is difficult because of the rarity of these pathognomonic presentations and the wide variety of presentations. Treatment of these infections is challenging as it lacks standardization. Herein, we report a case of chromoblastomycosis caused by Phialophora, in a 42-year-old immunocompetent male agriculturist from the humid and subtropical region of southern China. He had a 3-month history of pneumonia with intermittent fever, coughing, and expectoration. The infection subsequently spread to the bone and lymph nodes forming deep lesions and eventually resulting in osteolysis and lymphadenectasis. These subcutaneous nodules were observed after 9 months. Antifungal treatment was administered for 20 months leading to clinical improvement before the patient was lost to follow-up. This case is unique because such deep lesions are rare in immunocompetent individuals and because the initial onset was associated with pneumonia.